ENHANCING EMPLOYEE PRODUCTIVITY: THE ROLES OF STANDARD OPERATING PROCEDURES, JOB TRAINING, AND SOFT SKILLS - Indah Kusumawati; Ilma Darojat; Muh. Abdul Rosid (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the integrated influence of Standard Operating Procedures (SOPs), Job Training, and Soft Skills on employee productivity at PT. Panata Jaya Mandiri, an automotive component manufacturer in Indonesia. The research addresses the critical gap in understanding how these factors interact synergistically to drive sustainable productivity improvements in manufacturing settings. Using a quantitative approach, this research employed a cross-sectional survey design with 93 employees as respondents. Data were collected through structured questionnaires using a 5-point Likert scale and analyzed using SPSS version 26. Multiple regression analysis was conducted to test the hypotheses and determine the individual and combined effects of SOPs, job training, and soft skills on employee productivity. The results demonstrate that all three variables significantly influence employee productivity. SOPs account for 87.6% of productivity variance (R² = 0.876), job training explains 74.1% (R² = 0.741), and soft skills show the highest individual explanatory power at 88.8% (R² = 0.888). Collectively, these factors explain 95.2% of productivity variance (R² = 0.952), indicating a strong synergistic effect. The findings reveal that soft skills emerge as the most crucial individual factor in enhancing productivity. This research contributes to the existing literature by developing and validating an integrated productivity framework that synthesizes operational and human resource perspectives. Unlike previous studies that examined these factors in isolation, this study demonstrates their synergistic relationship, providing a comprehensive understanding of productivity drivers in manufacturing contexts. The findings offer valuable insights for manufacturing managers in emerging economies seeking to optimize their operational and human resource strategies simultaneously.